Taxonomia das espécies do subgrupo tridentata (Hymenoptera; Chalcididae, Conura) - Alpoim, Sâmia Lívia Testtzlaffe (2016)
The tridentata subgroup of Conura Spinola currently has only one described species - C. (Spilochalcis) tridentata Delvare, 1992. Here we propose fifteen other species, beside the former one. The diagnostic characters of tridentata subgroup and the original description of C. tridentata were reevaluated and changes are proposed to them. The amount of descriptive characters for the species is expanded to about three times more than the amount contained in original description of C. tridentata. New data about geographical distribution and association with hosts are presented. A identification key and illustrations are given for the recognition of all species.